Gender aspects of formation of value potential of students' physical training - O. Iu. Marchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: study of gender peculiarities of formation of valuable orientations of students in physical education and sport. Material: in research students of 3 - 11 classes of secondary schools (419), with which the survey was conducted, were involved. Results : the absence of students' understanding of the necessity of motor activity to human health. Also development of adolescents values of physical culture and sports. Showing psychosocial characteristics to form a stable interest in the physical self. It was found that 15% of girls wish to play hockey on grass, athletic gymnastics, football and boxing. Conclusions: for the formation of valuable orientations of physical culture among students it is necessary to consider not only the physiological, morphological and psychological aspects, but also gender peculiarities of personality.